Can hypothermic oxygenated perfusion (HOPE) rescue futile DCD liver grafts?. Issue 9 (September 2019) - Muller, X.; Schlegel, A.; Würdinger, M.; Wendt, M.; Kron, P.; Eshmuminov, D.; Müllhaupt, B.; Clavien, P.A.; Dutkowski, P.
Abstract: Background: The new UK-DCD-Risk-Score has been recently developed to predict graft loss in DCD liver transplantation. Donor-recipient combinations with a cumulative risk of >10 points were classified as futile and achieved an impaired one-year graft survival of <40%. The aim of this study was to show, if hypothermic oxygenated perfusion (HOPE) can rescue such extended DCD livers and improve outcomes. Methods: "Futile"-classified donor-recipient combinations were selected from our HOPE-treated human DCD liver cohort (01/2012-5/2017), with a minimum follow-up of one year. Main risk factors, which contribute to the classification "futile" include: elderly donors>60years, prolonged functional donor warm ischemia time (fDWIT > 30min), long cold ischemia time>6hrs, donor BMI>25 kg/m 2, advanced recipient age (>60years), MELD-score>25points and retransplantation status. Endpoints included all outcome measures during and after DCD LT. Results: Twenty-one donor-recipient combinations were classified futile (median UK-DCD-Risk-Score:11 points). The median donor age and fDWIT were 62 years and 36 min, respectively. After cold storage, livers underwent routine HOPE-treatment for 120 min. All grafts showed immediate function. One-year and 5-year tumor death censored graft survival was 86%. Conclusion: HOPE-treatment achieved excellent outcomes, despite high-risk donor and recipient combinations. Such easy, endischemic perfusion approach may open the door for an increased utilization of futile DCD livers in other countries.